Applied geophysics. U.S.S.R - Rast, Nicholas, 1927-2001 (Pergamon Press, 1962)
Applied Geophysics, U.S.S.R. illustrates a collection of selected papers that demonstrates methods in geophysical research. The journal presents the developments, done by Russian scientists, in the field of geophysics with bias toward the application of geophysical methods to the search for oil. The compendium is divided into four parts encompassing 17 chapters. The articles are grouped into topics that discuss seismic methods, gravimetry, electrical sonde methods, and geophysical methods of logging. Certain chapters focus on simplified methods for determining the intensities of purely long.